Distribution of biopsied non plaque-induced gingival lesions in a Chilean population according to the classification of periodontal diseases - Patricia Hernández-Ríos; Iris Espinoza; Macarena Salinas; Fernando Rodríguez-Castro; Mauricio Baeza; Marcela Hernández (BMC, 2018)
Abstract Background Many gingival lesions are not induced by plaque. The aim of this study was to analyze the frequency of biopsied non-plaque-induced gingival lesions (NPIGL) in a Chilean population. Methods One thousand twelve cases of biopsied gingival lesions with confirmed anatomopathologic diagnosis were included, from the records of the Oral Pathology Referral Institute (OPRI), Faculty of Dentistry, University of Chile, between years 1990 and 2009. Results The most frequent non plaque-induced gingival lesions categories from biopsied cases included hyperplastic lesions, malignancies and benign neoplasms. The most frequent diagnoses in each category were fibrous hyperplasia (35.47%), squamous cell carcinoma (3.85%) and giant cell fibroma (2.08%), respectively. From all lesions, only 8.3% fitted in the specified categories of the current classification of periodontal diseases. Conclusions The most frequent biopsied NPIGL were hyperplastic lesions and neoplasms. These categories represent relevant lesions to be included in a future periodontal classification system to improve the care needs of the patients, as well as early diagnosis and treatment.